2015
DOI: 10.1038/bmt.2015.273
|View full text |Cite
|
Sign up to set email alerts
|

Thiotepa-based high-dose therapy for autologous stem cell transplantation in lymphoma: a retrospective study from the EBMT

Abstract: on behalf of the EBMT Lymphoma Working PartyClinical information about thiotepa-based autologous stem cell transplantation (auto-SCT) outside the primary central nervous system lymphoma (PCNSL) field is sparse. In this registry-based retrospective study, we evaluated potential risks and benefits of thiotepa-based preparative regimens compared with BEAM (carmustine, etoposide, cytarabine, melphalan) in auto-SCT for diffuse large B-cell lymphoma (DLBCL, excluding PCNSL), follicular lymphoma (FL) or Hodgkin lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…The 100‐day and 1‐year NRM were 3.3% and 6.7%, respectively. These rates are similar to those reported in prospective clinical trials for rituximab + BEAM (4.1% 100‐day treatment‐related mortality, TRM) (Vose et al , ) and 131 I‐tositumomab/BEAM (4.9% 100‐day TRM) (Vose et al , ), and to those reported in recent registry‐based or non‐controlled studies of BEAM (4% 1‐year NRM) (Chen et al , ; Sellner et al , ), thiotepa‐based (2% 1‐year NRM) (Sellner et al , ) and fotemustine‐based (2.5% 100‐day and 5.9% 1‐year NRM) (Musso et al , , ) conditioning regimens. In the previous study by Visani et al () of BendaEAM conditioning, the 100‐day TRM was 0%.…”
Section: Discussionsupporting
confidence: 87%
“…The 100‐day and 1‐year NRM were 3.3% and 6.7%, respectively. These rates are similar to those reported in prospective clinical trials for rituximab + BEAM (4.1% 100‐day treatment‐related mortality, TRM) (Vose et al , ) and 131 I‐tositumomab/BEAM (4.9% 100‐day TRM) (Vose et al , ), and to those reported in recent registry‐based or non‐controlled studies of BEAM (4% 1‐year NRM) (Chen et al , ; Sellner et al , ), thiotepa‐based (2% 1‐year NRM) (Sellner et al , ) and fotemustine‐based (2.5% 100‐day and 5.9% 1‐year NRM) (Musso et al , , ) conditioning regimens. In the previous study by Visani et al () of BendaEAM conditioning, the 100‐day TRM was 0%.…”
Section: Discussionsupporting
confidence: 87%
“…18 While many of the grade ≥ 3 non-hematologic toxicities we noted are common after HDT-ASCT, our analysis demonstrates that TBC conditioning is associated with significantly more mucosal toxicity, infections and febrile neutropenia as compared to BEAM or thiotepa, etoposide, cytarabine, melphalan (TEAM). 19 Although their data analysis did not specify all subtypes of infection, the rates of viremia, viral organ disease, and immune-related toxicities we observed appear higher than expected after ASCT.…”
Section: Discussionmentioning
confidence: 63%
“…(Table 3) The European Society for the Blood and Marrow Transplantation (EBMT) working group performed a retrospective study using data from the EBMT database that included a subset analysis comparing R/R NHL patients given BEAM (n ¼ 199) or TEAM (n ¼ 110). [57] At around two years, PFS and OS were 62% versus 49% and 77% versus 77% in the BEAM and TEAM groups, respectively; there were no significant differences between groups. In the EBMT study, 87% of patients receiving TEAM were responsive to prior chemotherapy.…”
Section: Teammentioning
confidence: 89%
“…[57] To our knowledge, only one study has examined the efficacy and safety of the TEAM regimen. (Table 3) The European Society for the Blood and Marrow Transplantation (EBMT) working group performed a retrospective study using data from the EBMT database that included a subset analysis comparing R/R NHL patients given BEAM (n ¼ 199) or TEAM (n ¼ 110).…”
Section: Teammentioning
confidence: 99%